CaMKIIδ-dependent dysregulation of atrial Na+ homeostasis promotes pro-arrhythmic activity in an obstructive sleep apnea mouse model - Hegner, Philipp; Ofner, Florian; Schaner, Benedikt; Gugg, Mathias; Trum, Maximilian; Lauerer, Anna-Maria; Maier, Lars Siegfried; Arzt, Michael; Lebek, Simon; Wagner, Stefan (Frontiers in Pharmacology, 2024)
Background – Obstructive sleep apnea (OSA) is linked to a variety of pathologies including arrhythmias such as atrial fibrillation. Specific treatment options are mainly limited to symptomatic approaches. We have previously shown that increased production of reactive oxygen species (ROS) stimulates late sodium current through voltage-dependent Na+ channels via Ca2+/calmodulin-dependent protein kinase IIδ (CaMKIIδ), thereby increasing the propensity for arrhythmias. However, the impact on atrial intracellular Na+ homeostasis has never been demonstrated. Moreover, patients exhibit a broad variety of comorbidities, making it difficult to ascertain the effect of OSA alone. Objective – We analyzed the effect of OSA on ROS production, cytosolic Na+ levels and rate of spontaneous arrhythmias in atrial cardiomyocytes isolated from an OSA mouse model free of comorbidities. Methods – OSA was induced in C57BL/6 wildtype and CaMKIIδ knockout mice by polytetrafluorethylene (PTFE) injection into the tongue. After 8 weeks, atrial cardiomyocytes were analyzed for cytosolic and mitochondrial ROS production by confocal laser scanning microscopy. Cytosolic Na+ concentration and quantification of arrhythmias were performed by epifluorescence microscopy. Results – PTFE treatment resulted in increased cytosolic and mitochondrial ROS production. Importantly, in PTFE-treated mice, the cytosolic Na+ concentration was dramatically increased at various stimulation frequencies, while CaMKIIδ knockout mice were protected. In accordance, the rate of spontaneous Ca2+ release events was increased in wildtype PTFE mice whereas CaMKIIδ knockout impeded this effect. Conclusion – Atrial Na+ concentration and the propensity for spontaneous Ca2+ release events were increased in an OSA mouse model in a CaMKIIδ-dependent fashion, which may have therapeutic implications.